2020
DOI: 10.1002/ls.1518
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and tribological properties of eco‐friendly as‐exfoliated graphene in grease

Abstract: The exfoliation for few layers of graphene was prospective for scale output due to low cost and processable advantages. However, the massive production had some obstacles such as high pollution with organics and harmful elements and use of rare metal. Herein, we developed a facile and eco-friendly expansionreduction exfoliation method to prepare graphene from graphene oxide (GO) with aid of oxalic acid(H 2 C 2 O 4). The as-exfoliated graphene nanosheets possessed a 10-layered thickness and large lateral size o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
(89 reference statements)
0
2
0
Order By: Relevance
“…The test results showed that the friction reduction and wear-resistant properties were improved by 35.8 and 32.8%, respectively. 24 The alkylated graphene (AGN) was prepared and shown to possess excellent anti-wear and friction reduction properties in our previous work. 25 However, the boundary lubrication performance of AGN was not outstanding.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The test results showed that the friction reduction and wear-resistant properties were improved by 35.8 and 32.8%, respectively. 24 The alkylated graphene (AGN) was prepared and shown to possess excellent anti-wear and friction reduction properties in our previous work. 25 However, the boundary lubrication performance of AGN was not outstanding.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, they reported an eco-friendly expansion–reduction exfoliation method to prepare graphene from graphene oxide (GO) with the aid of oxalic acid (H 2 C 2 O 4 ). The test results showed that the friction reduction and wear-resistant properties were improved by 35.8 and 32.8%, respectively …”
Section: Introductionmentioning
confidence: 99%